Open anastomosis: an alternative for proximal vein graft anastomoses in significantly diseased aortas - Antunes, MJ (2009)
We describe a simple technique of constructing proximal vein graft anastomoses, in an open fashion, under brief periods of very low pump flows. We have used this technique without complications in more than 100 patients with significantly diseased ascending aorta wall. In our opinion, this technique is a good alternative to other, more complex, approaches often described.